Keamanan Hair Tonic Ekstrak Etanol, Fraksi Etanol, dan Fraksi Kloroform-Metanol dari Kayu Secang (Caesalpinia sappan L.) dengan Metode Uji Iritasi Primer dan HET-CAM - Sari, Dina Yuspita; Rahman, Ika Ristia (Jurnal Farmasi Udayana; Vol. 10, No 2, Tahun 2021DO - 10.24843/JFU.2021.v10.i02.p08, 2021)
Hair tonic is a hair care cosmetic to reduce hair loss, stimulate, and increase hair volume. Secang wood ( Caesalpinia sappan L.) has the potential to be developed as an active substance in hair tonic products because it contains flavonoids, polyphenols, including brazilin which are used to treat damage hair. To ensure the safety of hair tonic products, safety tests are required, including skin and eye irritation tests. This study aims to determine the safety of hair tonic formula of ethanol extract, ethanol fraction, and chloroform-methanol fraction from sappan wood. Ethanol extract, ethanol fraction, and chloroform-methanol fraction of sappan wood were formulated into hair tonic preparations. The hair tonic safety test includes: primary irritation test and eye irritation test using HET-CAM method. Based on the primary irritation test, the score of erythema and edema on the skin obtained a PII value of 0 (non-irritating category). The HET-CAM test on the three hair tonic formulas, positive control and negative control, showed that the positive control (lactic acid) resulted in an irritation score of 9.51 (strong irritation category); negative control (NaCl 0.9%) and the three hair tonic formulas had an irritation score of 0 (no irritation category). This indicates that the hair tonic formula from ethanol extract, ethanol fraction, and chloroform-methanol fraction of sappanwood is not irritating and safe to use. Keywords: HET-CAM, primary irritation test, sappan wood